Utilization of and Constraints on Animal Traction in Jigawa State, Nigeria - Ahmad, Desa; Abubakar, Mohammed Shu'aibu (INSInet Publication, 2010)
A survey was carried out to investigate the utilization of and constraints on animal traction in Hadejia Local Government Area of Jigawa State, Nigeria. Farmers having five hectares farm size and below were selected for the study. Farmers were categorized into four (4) groups based on their farm sizes, which are Group I – farmers having farm size equal to or less 1 hectare, Group II – farmers having farm size of 2 hectares, Group III – farmers having farm size between 3-4 hectares, Group IV – farmers having farm size of 5 hectares. Thirty (30) farmers were interviewed in each of the groups. A total of 120 sample data were collected and analysed using simple descriptive statistics. Data on breed types, implement and yoke used, source of the work animals, animal feeds and shelter were collected using structural questionnaire and oral interviews. The results showed that Sokoto Gudali bulls were the popular breed (73.3%) of cattle used by the respondents across the four groups while 26.7% of the respondents used White Fulani bulls. Source of work animals were mostly through personal purchased (45.8%) and loan by State Government (33.4%), while very few farmers acquired by inheritance (20.8%). Eighty percent of the respondents used Emcot and Kazaure animal drawn implement while 20% of the respondents used Arava and Strad. Yoke and rope were the common harness tools having 93.3% of the respondents using them while 6.7% of the respondents used combinations of yoke, rope and chain as harness tools. Work animals were training between 4-6 weeks before fully use for farm operations. Feeding of animals was mainly on free range during the rainy season and crop residues during the dry season. The constraints reported by the farmers include lack of funds, inadequate formal education, limited feed resources, few implements are used, disease treatment, lack of shelter for the animals and poor extension services. It was suggested that utilization of animal traction would be increased significantly if more fund are injected in animal traction technology by the state and local Government.